Main principles of expert quality report of medical care - Shvets Y. Y. (Interactive science, 2016)
this article describes the peculiarities of expert quality report of medical care as a mean of quality control on a modern stage of medical development in the country. Regulatory and methodical regulation of medical care testing in Russia has been analyzed and problematic aspects of its control have been found out.
Keywords: контроль; эксперт; экспертиза качества; контроль качества; медицинская помощь; control; medical care; качество медицинской услуги; quality of medical services; expert; quality testing; quality control